2017
DOI: 10.1021/acschembio.7b00389
|View full text |Cite
|
Sign up to set email alerts
|

Structure–Activity Relationships Reveal Key Features of 8-Oxoguanine: A Mismatch Detection by the MutY Glycosylase

Abstract: Base excision repair glycosylases locate and remove damaged bases in DNA with remarkable specificity. The MutY glycosylases, unusual for their excision of undamaged adenines mispaired to the oxidized base 8-oxoguanine (OG), must recognize both bases of the mispair in order to prevent promutagenic activity. Moreover, MutY must effectively find OG:A mismatches within the context of highly abundant and structurally similar T:A base pairs. Very little is known about the factors that initiate MutY’s interaction wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
61
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(65 citation statements)
references
References 49 publications
(151 reference statements)
4
61
0
Order By: Relevance
“…Structural studies show that B. stearothermophilus MutY makes contact with this face of the damaged base through a histidine residue that lies on a short C-terminal loop (41), and it has been suggested that this loop might be in proximity of the major groove in an undamaged DNA substrate (75). A study of E. coli MutY function on various substrate analogs found that the 2-amino group of 8-oxoG is critical for early recognition of an 8-oxoG:A damage site (84). Therefore, it is likely that MUTYH rapidly slides along DNA until the C-terminal domain encounters the 2-amino group of 8-oxoG, whereupon the enzyme stops, repositions, and further interrogates the damage site using the wedge residue.…”
Section: Discussionmentioning
confidence: 99%
“…Structural studies show that B. stearothermophilus MutY makes contact with this face of the damaged base through a histidine residue that lies on a short C-terminal loop (41), and it has been suggested that this loop might be in proximity of the major groove in an undamaged DNA substrate (75). A study of E. coli MutY function on various substrate analogs found that the 2-amino group of 8-oxoG is critical for early recognition of an 8-oxoG:A damage site (84). Therefore, it is likely that MUTYH rapidly slides along DNA until the C-terminal domain encounters the 2-amino group of 8-oxoG, whereupon the enzyme stops, repositions, and further interrogates the damage site using the wedge residue.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, inosine was found to be a possible candidate in this regard [29]. Other examples highlighting their use as tools to probe for biochemical mechanisms include, where 8-oxoinosine and other C8-subsituted purines have been employed to understand the base excision of 8-oxoG by the MutY glycosylases [30]; or in the replication of DNA with E. coli DNA polymerase I [31].…”
Section: Plos Onementioning
confidence: 99%
“…Mismatched bases of mtDNA damage originate from DNA replication errors, by either incorporation of wrong nucleotides or nucleotides mainly in oxidized bases [31]. Single base mismatches are identified by Y-box binding protein 1 (YB1) [32] and repaired by the mismatch repair system (MMR) [33]. DNA strand breaks includes single-strand (SSBs) [34] and double-strand breaks (DSBs) [35].…”
Section: Types Of Damagementioning
confidence: 99%